A Comparative Study on Traffic Impact Assessment - Abdul Qadir Jilani; Roohi Naeem; Rana Shoaib; Kashif Hussain; Saira Ashraf; Ammar Yasir (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This phenomenological study explores the lived experiences of urban commuters, aiming to understand the complexities of daily transportation struggles and resilience. Using in-depth interviews with 30 commuters in a metropolitan city, the research examined the emotional, social, and economic effects of transportation challenges on well-being. Thematic analysis revealed key themes: frustration with congestion, anxiety from uncertainty, and the resourcefulness of coping strategies. Narratives showed how transportation is deeply intertwined with work and personal life, shaping routines and affecting quality of life. Commuters described adaptive strategies to navigate and resist the stresses of urban mobility, from time management to emotional regulation. The findings offer a nuanced, contextualized view of urban commuting, contributing to the literature on transportation and mobility. This study underscores the importance of integrating commuter perspectives into urban planning, transportation policy, and community development, with the goal of improving livability, reducing stress, and promoting sustainable mobility in growing metropolitan areas.